Differences in Orthodontic Thermal Deflection of Nickel Titanium Wire in Artificial Saliva Soat And Isotonic Beverages - Suhartono, Budi; Yusuf, Moh; Aditya, Grahita; Wardhana, Erdianto Setya; Hadianto, Eko; Sa’adah, Fathimah Fitria (Odonto : Dental Journal, 2025)
Background: Deflection is one of the properties of the wire that can change if the environmental conditions in the oral cavity are acidic, caused by consuming isotonic drinks. This study aims to determine the difference in deflection of thermal nickel-titanium wire soaked in artificial saliva and isotonic drinks.Method: The type of research used was an in vitro experimental analytic study with a post-only control group design method. The sample used was 36 thermal nickel titanium wire (American Orthodontics) with a wire size of 0.016 inches and divided into 2 groups consisting of the artificial saliva group and the isotonic drink group. Soaking was carried out for 10.5 hours and stored in an incubator at 37oC, then a deflection test was carried out using a Universal Testing Machine. Analysis of the results was carried out using the Independent T-Test in each group after treatment.Result: The results of the study using the Independent T-Test showed a significant difference in the deflection value of the thermal nickel titanium wire in the artificial saliva group and the isotonic drink group of 0.000 (p<0.05).Conclusion: The conclusions obtained in this study indicate that thermal immersion of nickel-titanium wire in the artificial saliva group and the isotonic drink  group  affects  the  deflection  force  in  orthodontic  treatment.